Neonatal hearing screening program. Our results - González, Laura Díez (2010)
Aim: To evaluate the efficacy of the Vigo Newborn Hearing Screening Program in the early detection of hearing impairment and its impact in children with hearing loss in the achievement of communication and social skills.Material and Methods: We present the Newborn Screening Program in the Hospital Xeral Cíes de Vigo from August 2002 to December 2007. This program is a universal newborn hearing screening program based on four stages: screening, diagnosis, treatment and rehabilitation.Results: The participation rate in the screening program has grown gradually, reaching 99% coverage in 2007. The referral rate to the diagnostic stage was 0.2%, and the time between the screening test and the first evaluation in the Diagnosis Unity was 29 days. 14 of the 52 children referred to the second step were diagnosed; 7 were treated with cochlear implant, 5 were treated with hearing aids and 2 were treated with BAHA. They all have received early stimulation which has allowed in all cases an improvement of language skills as well as psychosocial development.Conclusions: It is essential the implementation of a Newborn Hearing Screening Program for early diagnosis and treatment that ensures children with hearing loss to achieve communication and social skills commensurate with their cognitive abilities.